Assessment of Quality of Life and Satisfaction Level of Parents of the Thalassemia Major Malnourished Patients - Muhammad Umair; Rafiq Ahmed Shahid; Tabassum Nawaz; Muhammad Adnan; Israr Khan; Mawra Hyder; Abdul Baqi Khan (Pakistan Journal of Medical Research)
Objective: To assess the quality of life & level of satisfaction among parents of the thalassemia major patients.